Effects of different N sources on riverine DIN export and retention in a subtropical high-standing island, Taiwan - Huang, Jr-Chuan (Biogeosciences, 2016)
Increases in nitrogen (N) availability and mobility resulting from anthropogenic activities have substantially altered the N cycle, both locally and globally. Taiwan characterized by the subtropical montane landscape with abundant rainfall, downwind of the most rapidly industrializing eastern coast of China, can be a demonstration site for extremely high N input and riverine DIN (dissolved inorganic N) export. We used 49 watersheds with similar climatic and landscape settings but classified into low, moderate, and highly disturbed categories based on population density to illustrate their differences in nitrogen inputs (through atmospheric N deposition, synthetic fertilizers, and human emission) and DIN export ratios. Our results showed that the island-wide average riverine DIN export is ~ 3800 kg N km(−2) yr(−1), approximately 18 times the global average. The average riverine DIN export ratios are 0.30−0.51, which are much higher than the averages of 0.20−0.25 of large rivers around the world, indicating excessive N input relative to ecosystem demand or retention capacity. The low disturbed watersheds have a high N retention capacity and DIN export ratios of 0.06−0.18 in spite of the high N input (~ 4900 kg N km(−2) yr(−1)). The high retention capacity is likely due to effective uptake by secondary forests in the watersheds. The moderately disturbed watersheds show a linear increase in DIN export with increases in total N inputs and mean DIN export ratios of 0.20 to 0.31. The main difference in land use between low and moderately disturbed watersheds is the greater proportion of agricultural land cover in the moderately disturbed watersheds. Thus, their greater DIN export could be attributed to N fertilizers used in the agricultural lands. The greater export ratios also imply that agricultural lands have a lower proportional N retention capacity and that reforestation could be an effective land management practice to reduce riverine DIN export. The export ratios of the highly disturbed watersheds are very high, 0.42–0.53, suggesting that much of the N input is transported downstream directly, and urges the need to increase the proportion of households connected to a sewage system and improve the effectiveness of wastewater treatment systems. The increases in the riverine DIN export ratio along the gradient of human disturbance also suggest a gradient in N saturation in subtropical Taiwan. Our results help to improve our understanding of factors controlling riverine DIN export and provide empirical evidence that calls for sound N emission/pollution control measures.